Zeolite-encapsulated single-atom catalysts for efficient CO2 conversion. Issue 54 (December 2021) - Alonso, Gerard; López, Estefanía; Huarte-Larrañaga, Fermín; Sayós, Ramón; Prats, Hector; Gamallo, Pablo
Graphical abstract: Highlights: Sc, Y, La, Ru, Rh, Ni, Pd, Pt@S-1 catalysts are great candidates for CO2 conversion. Redox mechanism is preferred by groups 3–9 TM s. Associative mechanism is preferred by group 10 T Ms. Groups 11−12 T Ms are predicted to have poor CO2 conversion catalytic activity. Abstract: Zeolite-supported single-atom catalysts (SACs) have emerged as a novel class of cheap and tuneable catalysts that can exhibit high activity, selectivity and stability. In this work, we conduct an extensive screening by means of density functional theory calculations to determine the usefulness of 3d, 4d and 5d transition metal (TM) SACs-supported in MFI-type Silicalite-1 zeolite for CO2 conversion. Two reaction mechanisms are considered, namely the redox - direct CO2 dissociation - and associative - hydrogen-assisted CO2 dissociation - mechanisms. Early TM SACs exhibit the lowest energy barriers, which follow the redox mechanism. These energy barriers raise when going right in the periodic table up to group 10, where they become prohibitive and the associative mechanism should dominate. By also considering their resistance to aggregation, we support the use of Sc, Y, La, Ru, Rh, Ni, Pd and Pt as potentially active and stable catalysts for CO2 conversion, given their low energy barriers and strong interaction with the zeolite framework.